"The significance of the GNRH 1 gene polymorphism (rs 6185, rs1812594) in the development of idiopathic hypogonadotropic hypogonadism." - Mavlonov U.Kh; Urmanova Yu.M; Khudaybergenov Sh.A; Khodzhaeva F.S. (Zien Journals, 2024)
The purpose of the study is to study the significance of the GNRH 1 gene polymorphism (rs 6185, rs1812594) in the development of idiopathic hypogonadotropic hypogonadism in boys and girls.
Keywords: idiopathic; hypogonadism; significance